UMPSA shares expertise in Industry Challenges and Innovative Solutions Matching Session - Ahmad Hilmy, Agir (UMPSA, 2025)
PEKAN, 25 February 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) organised the Industry Challenges and Innovative Solutions Matching Session to strengthen collaboration between academia and industry in addressing challenges and exploring innovation opportunities.